Influence Shift Work on Work Fatigue in Oil and Gas Industry Workers: Literature Review - Rezki Dwinda; Baiduri Widanarko (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Petroleum and gas industry carries out business in exploration and exploitation activities as well as in the processing of crude oil, an industry that is faced with working conditions and a high level of risk of danger. The work system for workers in the oil and gas sector applies the system shift like shift 4 time rotation, or two week days shift tends to make workers experience higher levels of fatigue and fatigue-related work accidents. For know the influence shift work on work fatigue in oil and gas industry workers. Method: This research uses the method literature review with the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). In the journal search carried out on database google scholar dan ScienceDirect with the keyword